Remote artificial eyes using micro-optical circuit for long-distance 3D imaging perception - Nopparat Thammawongsa; Preecha P Yupapin (My University, 2014)
A small-scale optical device incorporated with an optical nano-antenna is designed to operate as the remote artificial eye using a tiny conjugate mirror. A basic device known as a conjugate mirror can be formed using the artificial eye device, the partially reflected light intensities from input source are interfered and the 3D whispering gallery modes formed within the ring centers, which can be modulated and propagated to the object. The image pixel is obtained at the center ring and linked with the optic nerve in the remote area via the nano-antenna, which is useful for blind people.
Keywords: Conjugate; Photonic and Optical Devices